A Drug Combination Rescues Frataxin-Dependent Neural and Cardiac Pathophysiology in FA Models - Abeti, Rosella; Jasoliya, Mittal; Al-Mahdawi, Sahar; Pook, Mark; Gonzalez-Robles, Cristina; Hui, Chun Kiu; Cortopassi, Gino; Giunti, Paola (Frontiers in Molecular Biosciences, 2022)
Friedreich's ataxia (FA) is an inherited multisystemic neuro- and cardio-degenerative disorder. Seventy-four clinical trials are listed for FA (including past and present), but none are considered FDA/EMA-approved therapy. To date, FA therapeutic strategies have focused along two main lines using a single drug approach: a) increasing frataxin, b) enhancing downstream pathways, including antioxidants levels and mitochondrial function. Our novel strategy employed a combinatorial approach to screen approved compounds to determine if a combination of molecules provided an additive or synergistic benefit to FA cells and/or animal models. Eight single drug molecules were administered to FA fibroblast patient cells: Nicotinamide Riboside, Hemin, Betamethasone, Resveratrol, Epicatechin, histone deacetylase inhibitor 109, Methylene Blue, and Dimethyl fumarate. We measured their individual ability to induce FXN transcription and mitochondrial biogenesis in patient cells. Single-drug testing highlighted that Dimethyl fumarate, and Resveratrol increased these two parameters. In addition, the simultaneous administration of these two drugs was the most effective in terms of FXN mRNA and mitobiogenesis increase. Interestingly, this combination also improved mitochondrial functions and reduced reactive oxygen species in neurons and cardiomyocytes. Behavioural tests in a FA mouse model treated with Dimethyl fumarate and Resveratrol demonstrated improved Rotarod performance. Our data suggest that Dimethyl fumarate is effective as a single agent, and the addition of Resveratrol provides a further benefit in some assays without showing toxicity. Therefore, they could be a valuable combination to counteract FA pathophysiology. Further studies will help fully understand the potential of a combined therapeutic strategy in FA pathophysiology.